MEMBANGUN JIWA BERWIRAUSAHA UNTUK MENAMBAH PENGHASILAN KELUARGA IBU-IBU DI PIA ARDHIYA GARINI KOMPLEK GARUDA LANUD RSN PEKANBARU - Liga Febrina; Nia Anggraini; Erfa Okta Lussianda; Dodi Agusra; Jusmarni Jusmarni (JURNAL PENGABDIAN MANDIRI, 2022)
Mrs. Pia Ardhya Garini Garuda Air Base Complex RSN Pekanbaru is a forum for women's organizations with diverse educational backgrounds ranging from high school graduates to university graduates and most of them are housewives. Most of the mothers at Pia Ardhya Garini, Garuda Air Base Complex, RSN Pekanbaru, want to fill their free time with productive activities so they can increase their family income, because daily needs require increasing expenses. It is believed that the women of the Pekanbaru RSN Air Base complex have a lot of ability to increase their family income by having a productive business in their residential area. The women of the Pekanbaru RSN Air Base complex can be empowered as members of society who are classified as productive workers whose aim is to develop their entrepreneurial spirit and expand employment opportunities to increase family income. So, in connection with the efforts of the entrepreneurship development program to encourage the growth and development of Micro, Small and Medium Enterprises through various alternative activities, one of which is training and counseling to build an entrepreneurial spirit. The platform used as mentoring material is lectures, discussions and service learning. The training and counseling activities began with observations in the form of questions and answers with the women of Pia Ardhya Garini, Garuda Air Base RSN Complex, which was then continued with the provision of material. After that, training and counseling participants are provided with material and direct knowledge related to building an entrepreneurial spirit, then these activities are monitored and evaluated in order to strengthen the training participants in their understanding of the training and counseling material